Nail psoriasis: The journey so far - Alka Dogra; Amanjot Kaur Arora (Wolters Kluwer Medknow Publications, 2014)
Nail involvement is an extremely common feature of psoriasis and affects approximately 10-78% of psoriasis patients with 5-10% of patients having isolated nail psoriasis. However, it is often an overlooked feature in the management of nail psoriasis, despite the significant burden it places on the patients as a result of functional impairment of manual dexterity, pain, and psychological stress. Affected nail plates often thicken and crumble, and because they are very visible, patients tend to avoid normal day-to-day activities and social interactions. Importantly, 70-80% of patients with psoriatic arthritis have nail psoriasis. In this overview, we review the clinical manifestations of psoriasis affecting the nails, the common differential diagnosis of nail psoriasis, Nail Psoriasis Severity Index and the various diagnostic aids for diagnosing nail psoriasis especially, the cases with isolated nail involvement. We have also discussed the available treatment options, including the topical, physical, systemic, and biological modalities, in great detail in order to equip the present day dermatologist in dealing with a big clinical challenge, that is, management of nail psoriasis.